2009
DOI: 10.3329/bmrcb.v35i2.3020
|View full text |Cite
|
Sign up to set email alerts
|

Role of omega-3 fatty acid supplementation with indomethacin in suppression of disease activity in rheumatoid arthritis

Abstract: A study was conducted to see the diseases activity suppression role of omega-3 fatty acids with indomethacin in patients with rheumatoid arthritis. One group received indomethacin (75 mg) only daily while another group received indomethacin (75 mg) along with omega-3 fatty acids (3 g) daily for 12 weeks. The main outcome measures were DAS 2-28 joints score, number of swollen joints, number of tender joints, duration of morning stiffness, grip strength, pain VAS, patients global VAS, erythrocyte sedimentation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Review of reference lists of relevant publications identified three potentially relevant trials; one was included [ 40 ], and two could not be retrieved [ 41 , 42 ]. In total, 78 records describing 65 trials met the inclusion criteria for the systematic review; of these, 51 records describing 42 trials [ 40 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , …”
Section: Resultsmentioning
confidence: 99%
“…Review of reference lists of relevant publications identified three potentially relevant trials; one was included [ 40 ], and two could not be retrieved [ 41 , 42 ]. In total, 78 records describing 65 trials met the inclusion criteria for the systematic review; of these, 51 records describing 42 trials [ 40 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , …”
Section: Resultsmentioning
confidence: 99%
“…The others reported that daily supplementation of approximately 3 g n -3 PUFA for about three months was sufficient to achieve clinical improvements in these patients [38,39]. However, some meta-analyses have revealed no effect of n -3 PUFAs intake on the inflammation of joints, other clinical variables or the global assessment of RA patients [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, n-3 PUFAs composition of synovial fluid correlates positively with n-3 PUFA intake and negatively with the pain score [291]. The majority of clinical trials investigating the effects of n-3 PUFA supplementation showed clinical benefits in patients with ongoing disease [293,295,[321][322][323][324][325][326]. High n-3 PUFA intake protects against the incidence of RA [292][293][294] and improves RA prognosis [295,296].…”
Section: Rheumatic Diseasesmentioning
confidence: 99%